Maillard reaction between chitosan and xylan in ionic liquids. (3rd July 2020) - Deng, Weijie; Luo, Jiwen; Yan, Xiaomin
Abstract: Maillard reaction between chitosan and xylan was performed in common ionic liquid solvent at the first time. FT-IR, UV-visible spectrophotometry and fluorescence spectrometry were used to characterize the structures and the optical properties of the products. The results revealed that Maillard reaction happened when the mass ratios of chitosan to xylan were 1:1 and 1:3. In the FT-IR spectra, the new peaks at 1712 cm −1 and 802 cm −1 were belonged to absorption peaks of Maillard reaction products (MRPs). In the UV-visible and fluorescence spectra, there were the marking peak at 294 nm which belonged to furfural, and the fluorescence peak at 415 nm which corresponded to MRPs, respectively. Relatively high antibacterial activity and antioxidant property were also noted for the chitosan-xylan conjugate with mass ratio 1:1 as compared to native chitosan and xylan.